2016
DOI: 10.3233/jad-151028
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study of Plasma Exosomal Tau as a Potential Biomarker for Chronic Traumatic Encephalopathy

Abstract: Background Chronic traumatic encephalopathy (CTE) is a tauopathy associated with prior exposure to repetitive head impacts, such as those incurred through American football and other collision sports. Diagnosis is made through neuropathological examination. Many of the clinical features of CTE are common in the general population, with and without a history of head impact exposure, making clinical diagnosis difficult. As is now common in the diagnosis of other neurodegenerative disorders, such as Alzheimer's d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
124
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 145 publications
(125 citation statements)
references
References 80 publications
1
124
0
Order By: Relevance
“…Blood and cerebrospinal fluid (CSF) markers of central nervous system (CNS) injury may also provide insight to pathophysiological outcomes of RSBT and multiple mTBI. A recent study found a higher number of tau-positive exosomes in former American football athletes compared to retired non-collision sport athletes 40 . Alosco et al reported a weak correlation between head impact exposure and plasma total tau levels, but no relationship with clinical outcomes 41 .…”
Section: Repetitive Brain Trauma and Neurodegenerationmentioning
confidence: 92%
“…Blood and cerebrospinal fluid (CSF) markers of central nervous system (CNS) injury may also provide insight to pathophysiological outcomes of RSBT and multiple mTBI. A recent study found a higher number of tau-positive exosomes in former American football athletes compared to retired non-collision sport athletes 40 . Alosco et al reported a weak correlation between head impact exposure and plasma total tau levels, but no relationship with clinical outcomes 41 .…”
Section: Repetitive Brain Trauma and Neurodegenerationmentioning
confidence: 92%
“…Furthermore, although the scope of the current study was to characterise blood biomarkers for the purpose of advancing our understanding of human secondary injury pathophysiology, the findings of the current study warrant future investigations to evaluate the clinical potential of PRDX-6 in SRC diagnosis and prognosis; competitively evaluating the statistical performance of this marker against other well-studied indices of brain injury such as s100B and GFAP may be useful. Recent evidence suggests that peripherally measured Tau in the systemic circulation may reflect CNS tauopathy (42,43) or axonal damage (44). While we did not observe differences in T-tau levels between athletes with SRC and controls in the subacute time period, higher blood concentrations were associated with SRC at medical clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, EVs seem to play an important role in several diseases, such as cancer, neurodegenerative, cardiovascular, and metabolic diseases [21,22,23,24,25,26]. …”
Section: Introductionmentioning
confidence: 99%